Yield analysis and adaptation for Bacillus thuringiensis (Bt) and non-Bacillus thuringiensis (Bt) Cotton varieties in the kingdom of Eswatini - Khumalo, Daniel (International Journal of Environment, Agriculture and Biotechnology, 2019)
Cotton in Eswatini contributes 2.1 % of the country’s Gross Domestic Product owing to low cotton yield due to high pest pressure. Eswatini farmers grow Alba QM 301 a conventional non Bt variety which is affected by bollworm. Cotton is no longer profitable and farmers are quitting the industry, yet it is the only source of livelihood in drought prone areas of Eswatini. Countries like India and South Africa have replaced conventional cotton with high yielding Bt or genetically modified cotton.The study analyses yield and adaptation of Bt cotton under rain fed condition.Bt cotton hybrid was evaluated under field condition for adaptation and yield performance in 2016 and 2017 season. Two Bt cotton varieties JKCH 1947 Bt and JKCH 1050 Bt were tested against the local variety Alba Plus QM 301 and JKC 724 both Non Bt (NBt).JKCH 1947 recorded significantly higher seed cotton yield per ha of 3070 kg/ha on the first year. It was closely followed by JKCH 1050 with a yields of 2955 kg/ha.The number of boll per plant was also significant higher compared the control. Alba Plus QM 301 and JKC 724 both Non Bt (NBt) recorded the lower yields of 2066 and 821 kg/ha respectively, under the same condition with less number of bolls per plant. Similar observations were recorded on the second year, JKCH1947 and JKCH 1050 recording 1765kg/ha and 1865kg/ha respectively. A similar trend was observed onthe number of bolls per plant,higher number of bolls were recorded in JKCH 1050 Bt followed by JKCH 1947 Bt. Alba Plus QM 301 NBt and JKC 724 NBt recorded fewer boll in both years. All varieties showed good adaptability to local environment with good plant stand.